UKM2 Chlorella sp. strain electricity performance as bio-anode under different light wavelength in a biophotovoltaic cell - Aisyah Nadhirah Juhari,; Muhd Syazwan Sharani,; Wan Ramli Wan Daud,; Jafary, Tahereh; Mimi Hani Abu Bakar, (Penerbit Universiti Kebangsaan Malaysia, 2020)
A biophotovoltaic cell (BPV) is an electrobiochemical system that utilises a photosynthetic microorganism for instance is algae to trap sunlight energy and convert it into electricity. In this study, a local algae strain, UKM2 Chlorella sp. was grown in a BPV under different trophic conditions and light wavelengths. Once the acclimatisation phase succeeded, and biofilm formed, power generation by UKM2 algae at the autotrophic mode in synthetic Bold’s Basal media (BBM) under white, blue and red lights were tested. Polarisation and power curves were generated at these different conditions to study the bioelectrochemical performance of the system. Later, the condition switched to algal mixotrophic nutritional mode, with palm oil mill effluent (POME) as substrate. Maximum power generation obtained when using UKM2 in BBM under red light where a power density of 1.19 ± 0.16 W/m3 was obtained at 25.74 ± 3.89 A/m3 current density, while the open circuit voltage OCV reached 226.08 ± 8.71 mV. UKM2 in POME under blue light recorded maximum power density of 0.85 ± 0.18 W/m3 at current density of 16.75 ± 3.54 A/m3 , while the OCV reached 214.05 ± 23.82 mV. Chemical oxygen demand (COD) removal reached an efficiency of 35.93%, indicating the ability of wastewater treatment and electricity generation in BPV at the same time